Analisis Daya Dukung Pondasi Tower BTS Berdasarkan Uji Cone Penetrometer Test (CPT) - Elfira Resti Mulya; Fitro Darwis (Jurnal Ilmiah Wahana Pendidikan, 2020)
Determination of the type of foundation used depends on several factors that determine the hard soil, soil type, and the load that will be borne by the foundation. To calculate the soil bearing capacity is used on three methods of comparing based on SPT data, CPT is also based on laboratory data. This type of research is an analysis of soil carrying capacity analysis based on CPT field research results on the BTS Tower construction project in 2 locations, Sambiki Village and Hino Village, Morotai Island Regency. The field data obtained in the geotechnical engineering project consists of 2 CPT test points and 1 Hand Boring test point at each location. From the results of the sondir / CPT test at two different locations obtained from hard soil up to 7 meters for Sambiki Village and 6.8 m for Hino Village so that the next calculation for the bearing capacity of the foundation uses the bearing capacity of the borepile foundation. Based on the calculation of the ultimate bearing capacity of the borepile foundation (qult) with the use of the diameter of the drill pole calculated experiments vary between the diameter of the pole 20 cm, 30 cm, and 40 cm then for Sambiki Village the qult exchange rate or the carrying capacity of the foundation at a height of 7 m is 26.14 tons for pole diameter 20 cm, pole diameter 52.17 tons for diameter 30 cm and 86.83 tons for pole diameter 40 cm. Whereas for Sambiki Village in the 6.8 m section produces a limit of qult value of 24.62 tons for pole diameter of 20 cm, 48.71 tons for pole diameter of 30 cm and 80.66 tons for pole diameter of 40 cm.